How Women On Boards Can Drive Carbon Emission Disclosure With Carbon Tax Policy - Nurpratiwi, Tiara; Sri Mulatsih, Endang; Fikriyansyah, Ahmad (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
The purpose of this study is to investigate the role of women on board in influencing corporate carbon emissions disclosure, taking into account the impact of carbon tax implementation. This study utilizes both quantitative and qualitative approaches. Data analysis was conducted using panel data logistic regression. Quantitative data obtained from annual reports and sustainability reports of mining companies on the Indonesia Stock Exchange for the period 2016-2022 were compiled in a panel data format that includes cross-section and time series elements. A logistic regression analysis approach using STATA version 18 was used to test the relationship between the dependent variable, carbon emissions disclosure, and independent variables, such as the proportion of women on board and the proportion of female audit committee. Qualitative data was obtained through a literature review that discusses the impact of women's presence on boards of directors on carbon emissions disclosure in Asian countries. The study population is coal production sub-sector companies on the Indonesia Stock Exchange, with purposive sampling obtained a sample of 12 companies that meet the criteria related to consistency of listing and availability of annual reports. The result of this study is that the presence of Women on Board significantly supports the disclosure of carbon emissions in sub-sector mining companies in Indonesia, in line with similar findings in Asian countries. However, carbon tax policy is shown to weaken the relationship. Thus, further research is needed to investigate other factors that may influence carbon emissions disclosure in the mining industry and other sectors.